Pengaruh Konsetrasi Tawas terhadap Penurunan Kadar Fosfat Limbah Industri Penatu di Kota Cirebon - Supriyatin (Poltekkes Kemenkes Kendari, 2020)
The small industry of the laundry is exploding. The development of this industry needs to get attention because it is in the industry to dispose of the waste of residual production to the ditch or to the body of water without processing. Pollution to the environment can arise because of wastewater that contains many pollutants in the form of fats and other organic compounds derived from dirty clothing, some chemical compounds such as tripolyphosphate, detergent, and surfactants difficult to wave naturally in nature. This research knows the influence of the concentration of alum to decrease phosphate levels. This research uses a quantitative descriptive method against the remaining liquid wastes in the housing dumped into the water and sewer that flows to the area of the inhabitants. Determination of phosphate levels using UV-Vis spectrophotometers with Vanadate method at 410 nm wavelength. The results of the study showed an influence on the addition of alum to a certain concentration on phosphoric levels.